Acute suppurative thyroiditis in a post arteriovenous shunt infection patient - Ferdy Royland Marpaung; Aryati; Sidarti Soehita (Health for All Nations, 2022)
Acute suppurative thyroiditis (AST) is a rare clinical entity that must be treated immediately because of its morbidity, especially swelling in the thyroid area accompanied by fever. AST is often preceded by infection at another site; therefore, it is important to identify the source. A 40-year-old woman came to the Dr. Soetomo General Hospital complaining of pain and swelling in the neck, difficulty swallowing, and fever. The patient suffered from chronic kidney disease. One week before, she had an infected arteriovenous hemodialysis shunt. Laboratory results showed an increased fT4 (3.5 ug/dL) and a decreased TSH (0.015 uIU/mL), leukocytosis, and a raised C reactive protein (CRP). Thyroid ultrasound showed an abscess involving the entire left thyroid. Thyroid fine needle biopsy showed AST. Culture of the pus grew Staphylococcus aureus. The thyroid tests supported the diagnosis of AST with hyperthyroidism; immediate treatment was indicated. Three weeks after treatment, the patient was euthyroid and still had drainage of the wound. The AST was considered to be secondary to the hemodialysis AV shunt infection. Leukocytosis and increased CRP levels supported the presence of inflammation and culture grew Staphylococcus aureus. The patient improved with Clindamycin therapy. To our knowledge, this is the first AST case preceded by hemodialysis AV shunt infection.